Determinants of Unsafe Actions in Construction Workers of Hospital X Project in Semarang City - Damayanti, Erica Febi; Wahyuningsih, Anik Setyo (Indonesian Journal of Conservation, 2023)
The construction sector in Indonesia holds the top position with the highest rate of workplace accidents, accounting for 32% of all types of project-related work. This sector carries a high risk of workplace accidents, often due to unsafe actions. Unsafe actions are negligent behaviours exhibited by workers who disregard safety measures and can trigger workplace accidents. The construction project for Hospital X is a multi-story building in Semarang City. Based on observations, several unsafe actions have led to 5 workplace accidents from September 2022 to March 2023, with a medium severity level. This research aims to identify the factors related to unsafe actions. This study is an analytical observational research with a cross-sectional design. The total population consists of 80 field workers, and the sample selection utilizes Simple Random Sampling with a Slovin formula (5% error rate), resulting in 67 workers. Data analysis involves descriptive analysis and Chi-Square tests. The research findings indicate that 59.7% of workers engaged in unsafe actions. There is a significant correlation between age (p=0.002), length of service (p=0.001), knowledge of Occupational Health and Safety (K3) (p=0.000), K3 supervision (p=0.001), and K3 training (p=0.005) with unsafe actions.